AB0761 Follow-up of nailfold microvascular damage in mixed connective tissue disease versus systemic sclerosis patients. (12th June 2018) - Ferrari, G.; Sulli, A.; Pizzorni, C.; Ghio, M.; Patanè, M.; Paolino, S.; Trombetta, A.C.; Cutolo, M.
Abstract : Background: Nailfold videocapillaroscopy (NVC) is a non invasive diagnostic technique useful for evaluating microvascular status in patients with connective tissue diseases. 1 In systemic sclerosis (SSc) capillary abnormalities, when evaluated by NVC, evolve in a clearly defined sequence called the "scleroderma patterns" (Early, Active, Late). 2 On the contrary, mixed connective tissue disease (MCTD) doesn't show characteristic either nailfold capillary abnormalities or typical sequence. 1, 2 Until today, few studies described the main NVC changes in MCTD. 3 Objectives: To retrospectively study nailfold microangiopathy by NVC in MCTD patients with a follow-up of three years and to compare capillaries abnormalities between patients affected by MCTD and SSc. Methods: Ten patients (mean age 50±19 years) affected by MCTD with Raynaud phenomenon (Kasukawa's criteria) 4 who performed their first NVC were enrolled. Among these, complete capillaroscopic and clinical data at three years were available for 7 patients (disease duration 6.4±4.2 years). Main NVC parameters (absolute number of normal and total capillaries and scores of capillary ramifications, enlarged capillaries, giant capillaries, microhemorrhages, number of capillaries) were evaluated by NVC at baseline (T0, first NVC), and after one (T1) and three years (T3). Possible variations of capillary findings were analysed, along with correlations among capillaroscopic and clinical parameters. Furthermore, we compared main NVC parameters at T0 of ten above-mentioned MCTD patients versus ten random SSc patients with the same disease duration (6.4±4.2 years) and similar age (51±17 years). Statistical analysis was performed by non parametric tests. The patients were receiving different immunosuppressive treatments. Results: No statistically significant variation of the scores as well as of the absolute value of the above reported capillary parameters was observed during the 3 years of follow-up. No statistically significant correlation was observed between capillary parameters and MCTD clinical aspects (Raynaud phenomenon, dysphagia, dyspnoea, sclerodactily, sicca syndrome, telangiectasies and arthralgia) at first visit and during follow-up. The scores of enlarged capillaries and giant capillaries were found significantly higher (p<0.05) in patients with SSc versus MCTD patients at T0. Moreover, the absolute number of total capillaries and normal capillaries were found significantly lower (p<0.05) in SSc patients versus MCTD patients. On the contrary, no statistically significant difference was observed for the other capillary parameters (capillary ramification, microhemorrhages) between the two groups of patients. Conclusions: In a limited cohort of MCTD patients with an average disease duration of 6.4 years and a follow-up of three years, the nailfold microangiopathy does not seem to be significantly progressive. Patients with MCTD seem to show less enlarged/giant capillaries, and larger absolute number of total and normal capillaries than SSc patients. Still difficult to identify a defined NVC pattern in MCTD patients. References: [1] Cutolo M. et al. Best Pract Res Clin Rheumatol2008; 22:1093–108. [2] Cutolo M. et al. J Rheumatol. 2000; 27:155–60. [3] De Holanda Mafaldo DA, et al. Lupus. 2007; 16:254–8. [4] Cappelli S. et al. Semin Arthritis Rheum. 2012; 41:589–98. Disclosure of Interest: None declared